Biobriket Ampas Kelapa dan Testa Kelapa pada Variasi Konsentrasi Perekat Tepung Tapioka - Junianti, Fitri (Jurnal Serambi Engineering, 2026)
The extensive use of coconuts in the food industry generates large amounts of coconut pulp and coconut testa waste, which are generally underutilized and have the potential to cause environmental issues. One promising approach to utilizing this waste is by converting it into biobriquettes. In this study, biobriquettes made from coconut pulp and coconut testa were produced using tapioca starch adhesive at concentrations of 5% and 10% (w/w), and their quality was evaluated based on moisture content, ash content, and calorific value. The results showed that for coconut pulp biobriquettes, the addition of 5% adhesive produced the highest calorific value of 6446.28 Cal/g, while increasing the adhesive concentration to 10% reduced the calorific value to 6356.50 Cal/g and increased both moisture and ash contents. Conversely, in coconut testa biobriquettes, increasing the adhesive concentration enhanced the calorific value from 6485.78 Cal/g at 5% to 6897.58 Cal/g at 10%. All biobriquette variations exhibited moisture and ash contents below 8%, meeting the SNI 01-6235-2000 quality standard for briquettes. The best formulation was obtained from coconut testa biobriquettes with 10% tapioca starch addition.